2021
DOI: 10.28991/cej-2021-03091743
|View full text |Cite
|
Sign up to set email alerts
|

Measuring of Subjective and Objective Aesthetics in Planning and Urban Design

Abstract: The article includes the concept of aesthetics through what has been dealt with in the literature by philosophers and researchers who have addressed this concept in an attempt to derive indicators of aesthetics. The article adopted a descriptive and analytical methodology by reviewing recent literature on the concept of aesthetics and its relation to urban planning and design issues. Many subjective and objective aesthetics indicators have been identified, some of which are classified under real aesthetics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The building's harmony with its natural surroundings, green areas, waterways, or sea views nearby, will generate a set of sensations that can stimulate other mental activities [16]. It was also found that inspiration from nature is one of the indicators of beauty in planning and urban design [17]. In this sense, and according to literary reviews, the Hanging Gardens of Babylon may be the first and oldest biophilic model in the world, which meets all the principles and patterns of Biophilic design [18].…”
Section: The Biophilia and Biophilic Planningmentioning
confidence: 99%
“…The building's harmony with its natural surroundings, green areas, waterways, or sea views nearby, will generate a set of sensations that can stimulate other mental activities [16]. It was also found that inspiration from nature is one of the indicators of beauty in planning and urban design [17]. In this sense, and according to literary reviews, the Hanging Gardens of Babylon may be the first and oldest biophilic model in the world, which meets all the principles and patterns of Biophilic design [18].…”
Section: The Biophilia and Biophilic Planningmentioning
confidence: 99%
“…The traditional city of Najaf represents one of the important historical Iraqi cities, carrying many spiritual and religious values. These religious values, in addition to the social interaction and harmony between space users in this city, have led to a great deal of safety, in addition to some physical measures related to city planning [48,49].…”
Section: Public Space In An-najaf Traditional City (City Level)mentioning
confidence: 99%
“…• Social and economic inclusion: The trend seeks to achieve more efficient economic activities and benefits positively by creating a place to focus activities close to each other and resolving the tension between the complex and the place to spread economic prosperity and social stability. Densities with high population densities promote the creation of more jobs, the reduction of unemployment and poverty, and the provision of a high-quality standard of living by lowering family travel costs and raising income to get to a self-sufficient metropolis (Al-Salam et al, 2021;Woo, 2021), as shown in Table 1.…”
Section: Urban Sustainabilitymentioning
confidence: 99%